(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to analyze and synthesize the mastery micro-adaptive instruction model with problem-based learning to enhance digital technology skills for community college students. A total of 176 topics from local and international books, research papers, articles, and relevant documents were analyzed and synthesized using the systematic literature review method. Mastery of the aforementioned model for the community college students was obtained from the study results. The model was integrated from four bodies of knowledge; namely, (1) mastery learning, (2) micro learning, (3) adaptive learning, and (4) problem-based learning.